The Prognostic Value of C-reactive Protein to Albumin Ratio in Patients with Isolated Degenerative Aortic Valve Stenosis Undergoing Surgical Aortic Valve Replacement - Kahraman, Serkan (Braz J Cardiovasc Surg, 2020)
OBJECTIVE: To evaluate the prognostic value of C-reactive protein to albumin ratio (CAR) in patients with severe aortic valve stenosis undergoing surgical aortic valve replacement (AVR). METHODS: Four hundred seventy-six patients with severe degenerative aortic stenosis who underwent successful isolated surgical AVR were enrolled. Hospitalization due to heart failure, surgical aortic reoperation, paravalvular leakage rates, and long-term mortality were evaluated in the whole study group. The participants were divided into two groups, as 443 patients without mortality (group 1) and 33 patients with mortality (group 2) during the follow-up time. RESULTS: CAR was lower in patients without mortality than in those with mortality during the follow-up time (0.84 [0.03-23.43] vs. 2.50 [0.22-26.55], respectively, P<0.001). Age (odds ratio [OR]: 1.062, confidence interval [CI]: 1.012-1.114, P=0.014), CAR (OR: 1.221, CI: 1.125-1.325, P<0.001), ejection fraction (OR: 0.956, CI: 0.916-0.998, P=0.042), and valve type (OR: 2.634, CI: 1.045-6.638, P=0.040) were also found to be independent predictors of long-term mortality. Additionally, rehospitalization (0.86 [0.03-26.55] vs. 1.6 [0.17-24.05], P=0.006), aortic reoperation (0.87 [0.03-26.55] vs. 1.6 [0.20-23.43], P=0.016), and moderate to severe aortic paravalvular leakage (0.86 [0.03-26.55] vs. 1.86 [0.21-19.50], P=0.023) ratios were associated with higher CAR. CONCLUSION: It was firstly described that CAR was strongly related with increased mortality rates in patients with isolated severe aortic stenosis after surgical AVR. Additionally, rehospitalization, risk of paravalvular leakage, and aortic reoperation rates were higher in patients with increased CAR than in those without it.